Desain Ulang Pompa ESP Pada Sumur ”Umur” Lapangan WP - Wilson, Wilson; Firdaus, Firdaus; Sera, Rohima; Mukmin , M. Nur; Battu, Desianto Payung; Caesar, Abiyyu (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
Artificial Lift is an artificial lift method that is useful for increasing the pressure on the fluid so that it can flow to the surface. This method is used when the natural pressure of the well is no longer able to lift the fluid to the surface optimally. In the "W" well, artificial lift types have been installed, namely Gas Lift and Electrical Submersible Pump, but along with the production process the ability of the pump well will also decrease due to a decrease in pressure, so that optimization and redesign are necessary. The “W” well located in the “WP” field is considered necessary for optimization by redesigning the Electrical Submersible Pump. The redesign method is done by changing the type of method used to the Wiggins method. From the results of the Electrical Submersible Pump (ESP) design, it shows that the optimum flow rate obtained is 1560.8 bpd. Meanwhile, the type of pump used in the "W" well is REDA AN1500, which has an efficiency of 44%, while the motor used is a series 540 ( 30 HP, 435 volts, 45 A). The cable used is type 4 CU with a transformer with a size of 3 x 50 = 150 KVA and a DPH type 2 witchboard size 3. After selecting the components used, the next step is to calculate the total voltage from the results obtained. A total voltage value of 333.75 volts is still smaller than the available voltage, which is 600 volts, so you can be sure the pump can work properly.